Somatic Experiencing® Informed Therapeutic Group for the Care and Treatment of Biopsychosocial Effects upon a Gender Diverse Identity - Briggs, Paul C.; Hayes, Sage; Changaris, Michael (Frontiers in Psychiatry, 2018)
Abstract Background: Somatic Experiencing® (SE™) is a resiliency-based treatment for autonomic nervous systems (ANS) dysregulation syndromes such as post-traumatic stress disorder, anxiety, depression, and physical syndromes like chronic pain, migraines, and fibromyalgia. “Transgender/gender non-conforming/gender variant" describes people whose gender identity/expression is different, at least part of the time, from the sex assigned at birth. Research indicates transgender individuals have a higher incidence of depression, anxiety, victimization, and discrimination. SE™ tools may support transgender/gender non-conforming individuals to increase resilience in the face of discrimination and social injustice. Methods: This study is a pre-test post-test within group (N=7) pilot study assessed the impact of a 10 session SE™ based group treatment on depression (PHQ9), anxiety (GAD7), somatic symptoms (PHQ15), quality of life (WHOQoL-BREF), coping with discrimination (CDS) for a cohort of seven individuals identifying as transgender/gender non-conforming. Materials were created in collaboration with members of the LGBT community. Care was taken to be inclusive of gender non-conforming identities and culturally responsive in design. Results: Participants described their gender identities as: non-binary, female to male, male to female, and gender fluid. Participants had significant increase in psychological quality of life (psychological well-being) (WHOQoL-BREF) p = .004, SD = 2.31, with a modest effect size of d = .71. Some likely impacts of historical effect discussed. No other clinical or quality of life outcomes were statistically significant. However, one outlier was identified in the dataset. When this outlier was excluded there was a trend towards significant reduction in depression symptoms (PhQ9) p = .097, SD = 3.31 and a modest effect size of d = .68; somatic symptoms (PhQ15) p = .093, SD = 3.52 and a modest effect size of d = .72. Conclusions: These data indicate that a brief 10 session intervention of SE™ could have a meaningful impact on symptoms of depression, somatization, and QoL for gender non-conforming individuals. Further research is warranted. Limitations: First this study has a small sample size limiting statistical power and generalizability. Second is a history effect. Less than one week prior to final data collection there was a significant hate-motivated act in Florida targeting the